Oral ferroportin inhibitor vamifeport for improving iron homeostasis and erythropoiesis in β-thalassemia: current evidence and future clinical development. Issue 7 (3rd July 2021) - Porter, John; Taher, Ali; Viprakasit, Vip; Kattamis, Antonis; Coates, Thomas D; Garbowski, Maciej; Dürrenberger, Franz; Manolova, Vania; Richard, Frank; Cappellini, M. Domenica
ABSTRACT: Introduction: In β-thalassemia, imbalanced globin synthesis causes reduced red blood cell survival and ineffective erythropoiesis. Suppressed hepcidin levels increase ferroportin-mediated iron transport in enterocytes, causing increased iron absorption and potentially iron overload. Low hepcidin also stimulates ferroportin-mediated iron release from macrophages, increasing transferrin saturation (TSAT), potentially forming non-transferrin-bound iron, which can be toxic. Modulating the hepcidin–ferroportin axis is an attractive strategy to improve ineffective erythropoiesis and limit the potential tissue damage resulting from iron overload. There are no oral β-thalassemia treatments that consistently ameliorate anemia and prevent iron overload. Areas covered: The preclinical and clinical development of vamifeport (VIT-2763), a novel ferroportin inhibitor, was reviewed. PubMed, EMBASE and ClinicalTrials.gov were searched using the search term 'VIT-2763ʹ. Expert opinion: Vamifeport is the first oral ferroportin inhibitor in clinical development. In healthy volunteers, vamifeport had comparable safety to placebo, was well tolerated and rapidly decreased iron levels and reduced TSAT, consistent with observations in preclinical models. Data from ongoing/planned Phase II studies are critical to define its potential in β-thalassemia and other conditions associated with iron overabsorption and/or ineffective erythropoiesis. If vamifeport potentially increases hemoglobin and reduces iron-related parameters, it could be a suitable treatment for non-transfusion-dependent and transfusion-dependent β-thalassemia.